Comprehensive assessment of fatty acid profiles of meat products to develop action plan strategies for healthier products - Sakineh Yazdanparast; Fatemeh Mohammadi-Nasrabadi; Ali Hashmati; Roghayeh Rezazadeh; Mehdi Taheri; Barbod Alhouei; Fatemeh Esfarjani (Scientific Reports)
Abstract The global consumption of processed meat products has increased over the last few years. This study aimed to comprehensively evaluate the fatty acid profile of meat products to propose action plan strategies for the food industry, particularly for processed meat producers. This cross-sectional study investigated the fatty acid profile of the most consumed meat products in Tehran, Iran (2024). Sixty samples (twenty brands) were randomly selected from food chain stores across five districts and stored according to labeled instructions. Fat was extracted and analyzed for total content and fatty acid profile via Folch method adaptation and gas chromatography (GC), respectively. Statistical analysis via one-way ANOVA and Tukey’s test (p < 0.05) was performed via SPSS version 20 (SPSS, Chicago, IL). The total fat content of the products varied significantly (ranging from 13.34 to 21.23%), with 16% of the products exceeding national standards. The trans fatty acid (TFA) content varied from 0.51 to 3.77% fat. The levels of 2% TFA in the products were greater than the allowed content. Beef hamburger (50.38%) and German sausage (20.79%) had the highest and lowest saturated fatty acid (SFA) contents, respectively. The SFA content also differed among products, with palmitic acid being the most abundant. Oleic acid (37.04% in loghmeh kebab) and linoleic acid (44.31% in sausage) were the dominant MUFAs and PUFAs. The imbalanced n-6/n-3 ratio and variations in the MUFA/PUFA and PUFA/SFA ratios further emphasize the need for improvement. The action plan strategies have been placed on this issue to facilitate policymakers’ decisions to implement healthier meat products to promote public health. Collaborative efforts from policymakers (regulations, consumer education) and the food industry, particularly processed meat producers (reformulation, fat substitution, labeling), are essential to create a healthier fatty acid profile in these products. Without these regulatory advancements, the creation of healthier meat products may remain unattainable.